Prévalence des maladies diarrhéiques et facteurs associés dans les ménages de la ville d’Isiro en Province du Haut-Uélé - Albert, Wembakoy Okolongo; Louison, Lohombo Emongo; Papy, Moto Moustafa; Zoé-Arthur, Kazadi Malumba; Eugene, Basandja Longembe; Joris, Losimba Likwela (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
INTRODUCTIONThis study was conducted to determine the prevalence of diarrheal diseases and associated factors in households in the Isiro health zone. METHODAn analytical cross-sectional study was conducted in 384 households from December 1 to 14, 2020. Data were collected through guided interviews of mothers and caregivers of children under 5 years old. Data analysis was done using SPSS 20 and STATA 13 software. The prevalence of diarrhea was calculated, the analysis of factors associated with diarrhea was done using step-by-step logistic regression. not descending and the strength of association was estimated using the adjusted ORs.RESULTSThe overall prevalence of diarrhea was 6.54 (95% CI: 5.7-7.4); in children under 5, it was 14.57 (95% CI: 12.1-17). This prevalence was higher in rural areas (p <0.05). Care in the health facility was higher in rural areas (78.8%) and home treatment in urban areas (92.2%) (p <0.05). Home water treatment (aOR = 0.206; p <0.05) and improved source use (aOR = 0.435; p <0.05) protect against diarrhea. Long access to water and lack of awareness about diarrhea increased the risk of diarrhea more than twice (p <0.05).CONCLUSIONDiarrheal diseases are frequent in households and higher in rural areas. They are taken care of differently depending on the place of residence. The treatment of water, the use of improved water sources, the reduction of access times and the sensitization of mothers are actions to be promoted.